Developing Interactive Learning Media to Enhance Elementary School Students’ Learning Motivation - Ningsi, Ningsi; Hartono, Hartono (EDUCARE: Journal of Primary Education, 2025)
The low learning motivation among elementary school students remains a major challenge in the learning process. Conventional methods, which are often unengaging, make students quickly bored and passive. Therefore, the development of interactive learning media is needed to effectively and enjoyably enhance student involvement, interest, and enthusiasm. This study uses the Research and Development (R&D) method with the ADDIE model to develop interactive learning media. The development process includes needs analysis, learning strategy design, media creation, implementation, and effectiveness evaluation. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed both qualitatively and quantitatively to assess the quality and effectiveness of the developed learning product. The implementation of interactive learning media has proven effective in increasing student motivation and engagement. The use of physical components, such as wooden map boards and cultural picture cards, provided a hands-on learning experience that deepened students' understanding. Despite challenges related to teacher adaptation and media accessibility, the benefits of this approach—especially in improving motivation and learning outcomes—are evident. Future research should explore the long-term impact on student knowledge retention and how to adapt the media for diverse cultural contexts. This study significantly contributes to the development of interactive learning media that can enhance student motivation and engagement in elementary education. By integrating physical components that support active learning, this research offers a new, effective approach for teaching cultural diversity. Additionally, it provides insights into the development of more adaptive and applicable media that can be implemented in various cultural contexts and used more widely in classrooms.